2022
DOI: 10.3390/ijerph19084487
|View full text |Cite
|
Sign up to set email alerts
|

Immigrant Status and Ethnic Inequities in Dental Caries in Children: Bilbao, Spain

Abstract: This study examined the migratory status/ethnic inequities in dental caries in school children aged 4–9 years (n = 1388) and the impact of the Children’s Oral Health Program in the Municipality of Bilbao in the Basque Country Region, Spain. Using the 2017 Children’s Oral Health Survey, log binomial regression was used to quantify the association of parental immigration status/ethnicity with tooth decay for (1) the primary and the permanent dentitions, separately, in children 4–9 years old; and (2) for the perm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…25,26 However, other studies have shown that ethnic inequalities in child oral health persist despite the fact ethnic groups are disproportionately overrepresented in the lower socioeconomic groups. 27,28 Consequently, it is crucial to establish to what extent socioeconomic factors might explain ethnic differences in child oral health behaviours, as this might depend on the setting. No similar evaluation has been carried out in relation to child oral health behaviours.…”
Section: Introductionmentioning
confidence: 99%
“…25,26 However, other studies have shown that ethnic inequalities in child oral health persist despite the fact ethnic groups are disproportionately overrepresented in the lower socioeconomic groups. 27,28 Consequently, it is crucial to establish to what extent socioeconomic factors might explain ethnic differences in child oral health behaviours, as this might depend on the setting. No similar evaluation has been carried out in relation to child oral health behaviours.…”
Section: Introductionmentioning
confidence: 99%